Nauki społeczne w perspektywie nowoczesnej biurokracji i ponowoczesnej refleksyjności - wybrane konteksty parametryzacji nauki = Social sciences in the perspective of modern bureaucracy and postmodern reflexivity - selected contexts of science parametrization - Bielska, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Knowledge is treated as a consumer goods in the postindustrial society. It has to be utilitarian, innovative, practiced on the verge of risk, and effective. Furthermore, it is to function within the global market of research results exchange. In such a situation, ambivalences and controversies concerning university status, knowledge as a set of goods created at universities, and functions socially assigned to them appear.
Keywords: uniwersytet; parametryzacja; późna nowoczesność; biurokracja; refleksyjność; audyt; university; parametrization; late modernity; bureaucracy; reflexivity; audit